Estudo genético do escore de condição corporal de vacas Nelore - Fernandes, Anna Flávia de Araujo [UNESP] (2015)
The body condition may be related to meat production efficiency and maternal ability. Until now, knowledge of the relationship between body condition score (BCS) and productive performance characteristics is scarce for Zebu animals. The objectives of this study were to demonstrate the importance of assessment of body condition, investigate the performance long yearling as an indicator of body condition, quantify the relationship between the BCS and the adult size and check the possibility of including BCS in selection index of Nellore cows. The BCS is assigned in the diagnosis of pregnancy or weaning, ranging from 1 to 5 points. In the model analysis for BCS, we considered the following systemic effects: contemporary group (CG), birth order, adult weight (excluding the analysis with long yearling weight), age at first calving (excluded in the analysis of age at first calving ), calf weaning weight (WW). They were included in the model long yearling weight (YW) the effects of CG and age at yearling (linear and quadratic effects). In models of visual scores of conformation (C), early finishing (EF), muscling (M) and weight gain from weaning to long yearling (WG), it was considered: CG effects, age at yearling (linear and quadratic effects) and cow age at calving (linear and quadratic effects). In the long yearling hip height model (YH) included the effects of CG, age at long yearling (linear and quadratic effects) and cow age at calving (linear effect). The model of mature weight (MW) included the effects of CG, age at first calving, age at weighing (linear and quadratic effects) and WW. For mature hip height (MH) were considered the effects of CG and age at first calving (linear). For age analysis at first calving (AFC) only the effect of CG considered. To reconception (REC), included the effects of CG, MW, AFC, calving interval (CI) and WW. In CI model, the effects of CG, gestational stage, AFC, MW and WW were included. Through ...